2021
DOI: 10.5709/ce.1897-9254.437
|View full text |Cite
|
Sign up to set email alerts
|

How have COVID-19 Confirmed Cases and Deaths Affected Stock Markets? Evidence from Nigeria

Abstract: This study assesses the effect of COVID-19 proxied by the number of confirmed cases of the infection and deaths on Nigeria’s stock market over the 23rd March to 11th September 2020 period using the autoregressive distributed lag (ARDL), canonical cointegrating regression (CCR), dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) techniques. The bounds test to cointegration result reveals that a long-run relationship exists between COVID-19 and Nigeria’s stock market (along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Given the fact that COVID-19 confirmed deaths come as a result of the virus infection, it follows that stock market participants must have reacted to the confirmed cases earlier than the documented deaths. Similar results are reported by various scholars, such as Abu et al [ 2 ], Ashraf [ 10 ], Al-Awadhi et al [ 4 ], Ru et al [ 30 ], Alber [ 5 ], among others, who documented that returns on stock markets appear to be more susceptible to confirmed COVID-19 cases than reported deaths. Our results, however, are contrary to findings in Babarinde [ 12 ], who document that all the measures of COVID-19 confirmed cases and deaths do not statistically and significantly explain stock prices in Nigeria.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Given the fact that COVID-19 confirmed deaths come as a result of the virus infection, it follows that stock market participants must have reacted to the confirmed cases earlier than the documented deaths. Similar results are reported by various scholars, such as Abu et al [ 2 ], Ashraf [ 10 ], Al-Awadhi et al [ 4 ], Ru et al [ 30 ], Alber [ 5 ], among others, who documented that returns on stock markets appear to be more susceptible to confirmed COVID-19 cases than reported deaths. Our results, however, are contrary to findings in Babarinde [ 12 ], who document that all the measures of COVID-19 confirmed cases and deaths do not statistically and significantly explain stock prices in Nigeria.…”
Section: Resultssupporting
confidence: 88%
“…Most of the studies above focused on advanced economies and some developing and emerging market. In Nigeria, only few studies had assessed the impact of COVID-19 pandemic on stock market returns (see [ 2 ], Babarinde, et al 2020). Albeit, these studies only focused on how COVID-19 cases and deaths affect stock markets without taking into consideration the policy measures taking by government to contain the spread of the virus, the measures, especially the lockdown that have crippled the economic activities affect stock markets.…”
Section: Introductionmentioning
confidence: 99%
“…The negative and positive effects of number of confirmed cases and number of deaths respectively on volume of stocks traded are both insignificant. However, the number of discharged cases exerts a negative and significant effect on volume of stocks traded for the banks, hence agrees with the apriori expectation.This is in agreement with the mixed results found by [24] and [25] but sharply contradict [13,1,8].…”
Section: Summary Of Findings Conclusion and Recommenda-tionssupporting
confidence: 92%
“…For obvious reason (newness of the covid pandemic) in Nigeria, few empirical research exist that examine effect of Covid-19 pandemic on stock prices and development in the capital market. [25] in a study to examine how Covid-19 deaths and cases impacted on activities in the Nigerian Stock Exchange (NSE) between March and September 2020 with ARDL and other econometric techniques, found that while confirmed cases of Covid-19 affected the market negatively, number of deaths positively affected it during the period. [26] conducted research aimed at ascertaining how covid-19 affected the Nigerian Stock Exchange from January to April, 2020 using the E-GARCH and Q-GARCH models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hazem et al (2021) showed that the COVID-19 incidents had a negative impact on equity movement significantly, moreover, the U.S. lockdown and interest rate changes are the most affected by the G8 equity transactions, followed by Germany, France and the UK. Abu et al (2021) found that the number of confirmed cases of COVID-19 had a negative impact on stock market, however, the number of deaths had a positive one in the long-term. Nwosa (2021) indicated that COVID-19 had negative impacts on oil price, exchange rate and stock market performance in Nigeria.…”
Section: Existing Studiesmentioning
confidence: 95%